Inovasi Bisnis : Upaya Adaptasi UKM Werkudoro di Era Adaptasi Kebiasaan Baru - Kusnandar Kusnandar; Mohamad Harisudin; Nuning Setyowati; Raden Kunto Adi; Raden Rara Aulia Qonita; Isti Khomah (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2020)
The Covid-19 pandemic has a major impact on various sectors of life, including Small and Mid-size Enterprises (SMEs). The government makes various policies, one of which is the implementation of the New Normal. SMEs must adapt to New Normal conditions. SMEs Werkudoro is one of the SMEs in the Sukoharjo Regency. To face this New Normal condition, SMEs Werkudoro has several problems. The problem is that the packaging label is not marketable, product packaging is not marketable, wrap the packaging with stapler and SMEs are less developed. The method used are socialization, introduction, training and accompaniment. Community service activities are improvement marketable packaging labels, introducing marketable packaging with standing pouches, introducing of plastic sealers, repairing of product banner and business innovation training. Community service activities give knowledge for SMEs and benefits for adaptation in the New Normal condition, so they can survive and can develop.